Experimental study of the flow dynamics and thermodynamic properties of a tube in vertical falling film evaporator for data center cabinets - Ganglin Cao; Xiaoteng Min; Wenrui Xi; Shaojie Wu; Shuzhi Zhang; Guoqiang Liu; Xiongwen Zhang; Kuang Yan (Case Studies in Thermal Engineering, 2023)
This study presents an innovative integrated structure that combines a cabinet with a vertical falling film evaporator, enabling efficient natural evaporative cooling and effectively reducing energy loss in data centers. To in-depth understand the proposed structure's cooling mechanism, a novel inserted liquid film distributor is initially devised in the experiment, which can make the water flowing into the tube form an intact liquid film. Then, the visualization experiments are carried out in the tube to observe the water film flow dynamics, demonstrating that a minimum spray density of 0.048 kg·m−1·s−1 can be attained while maintaining liquid film integrity. Meanwhile, when the vibration frequency reaches 2700 Hz, a significant water film rupture in the tube occurs. Finally, building upon the experimental result analysis, at a spray density increment of 0.024 kg·m−1·s−1, the maximum increments of heat transfer rate and heat transfer coefficient corresponding to the intact liquid film are 16.2% and 23.3%, respectively. By contrast, those two indexes corresponding to the ruptured liquid film are 63.4% and 50.9%, respectively. This research provides reliable guidance and valuable insights for the design and efficient operation of natural evaporation falling film evaporators.